Preparation of Hydroxyapatite/Zirconia Porous Composites via Polymeric Sponge Method and Study the Physical and Bioactivity Properties. Issue 1 (March 2020) - Mohammad, M; Taha, A; Shahatha, S
Abstract: In this study, Hydroxyapatite/Zirconia porous composites at different ratio were fabricated by polymeric sponge method. HAp were produced via solid state reaction in molar ratio (3:2) between TCP and Ca(OH)2 . The crystal structure of the samples were characterized using X-ray diffractometer (XRD), scanning electron microscopy (SEM). Furthermore, the porosity and rheological properties of the samples were also tested. It's found that the compression strength with the highest value (13.2 MPa) obtained when the composition ratio is (30:70 wt %) and porosity (65.7%). Incubated for 30 days in Simulation Body Fluid, a bone like apatite layer was completely formed on the surface of the porous composite.